2021
DOI: 10.1016/j.jshs.2021.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of proprioception, cutaneous sensitivity, and muscle strength with the balance control among older adults

Abstract: Highlights Weak to moderate correlation between: Ankle plantar/dorsiflexion proprioception and dynamic balance control as measured by the Berg Balance Scale. Ankle plantar/dorsiflexion, hip abduction, and muscle strength and dynamic balance control as measured by the Berg Balance Scale. Knee flexion proprioception along with cutaneous sensitivity at great toe/arch and static balance control as measured by the root mean squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
2
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 63 publications
8
60
2
5
Order By: Relevance
“…Previous studies confirmed JPS only with dorsiflexion; however, in this study, we confirmed JPS and FS by performing both dorsiflexion and plantarflexion, and found conflicting results between dorsiflexion and plantarflexion [9,10,[21][22][23].…”
Section: Discussioncontrasting
confidence: 49%
“…Previous studies confirmed JPS only with dorsiflexion; however, in this study, we confirmed JPS and FS by performing both dorsiflexion and plantarflexion, and found conflicting results between dorsiflexion and plantarflexion [9,10,[21][22][23].…”
Section: Discussioncontrasting
confidence: 49%
“…Because this study specifically recruited participants with plantar calluses, our values are presumably greater than the mean of shod populations of the same age in Germany and other industrialized countries. Initial MTs, particularly in IG, was higher and therefore indicate less sensitivity than the values of 2.5–6.6 g documented so far in the heel region (Billot et al, 2013 ; Jain et al, 2008 ; Perry, 2006 ; Song et al, 2021 ). Since the existence of callused skin is the main difference between our sample and prior study samples, a relationship between monofilament sensitivity and skin properties is a potential explanation for this offset.…”
Section: Discussionmentioning
confidence: 66%
“…Muscle strength required to maintain balance is less when stationary than in functional movement. QipengSong et al (2021) indicated that muscle strength was correlated with dynamic balance but not static balance [ 31 ]. In addition, hip muscles correct large errors, while ankle muscles correct minor errors.…”
Section: Discussionmentioning
confidence: 99%